Housing market differentiation: the cases of Yenimahalle and Çankaya in Ankara - Alkan, Leyla (International Journal of Strategic Property Management, 2015)
This study aims to investigate housing market differentiation, drawing upon the results of case studies of the Çankaya and Yenimahalle districts that adopt a set of statistical techniques. As a first step, a cluster analysis is carried out to identify whether identifiable clusters of housing attributes exist on the basis of neighborhoods. Next, a Multiple Discriminant Analysis (MDA) is applied to investigate the differences between clusters, and to understand which housing attributes contribute most to submarket separation. Finally, a hedonic price analysis is conducted for each cluster and for the overall market to identify price differences in the housing market. The results of the study support the hypothesis that the housing market is segmented in Yenimahalle and Çankaya, and that location is the main determining factor in this segmented structure of different house values. The study also reveals that within this segmented structure, each cluster has its own dynamics, and that the price formation in each cluster is dependent on different variables.First Publish Online: 1 Apr 2015